PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS METODE PEMECAHAN MASALAH PADA MATERI SEGITIGA - Tuty Pratiwi; Rusdy A. Siroj; Muslimin M. (LP4MK STKIP PGRI Lubuklinggau, 2018)
The aims of this study is to produce Student Work Sheets based on problem solving methods in triangle material which is valid and practically. The research method is development research. This development research consist of two stages, that is preliminary stage and the formative evaluation stage. Based on product analysis results, Student Work Sheets were obtained based on valid and practical problem solving methods. Valid can be seen from the results of the expert evaluation (validator), while practically seen from the results of the trial of the small group of students in completing the given LKS. Based on data analysis of student learning outcomes obtained an average value of 75.70, which means student learning outcomes in triangle material classified as good categories, it is concluded that the Student Work Sheets that have been developed have potential effects.